Cytokine genotyping (TNF and IL-10) in patients with celiac disease and selective IgA deficiency - Cataldo, F; Lio, D; Marino, V; Scola, L; Crivello, A; Mulè, A.M; Corazza, G.R (The American journal of gastroenterology, 2003)
Selective IgA deficiency (IgAD) and celiac disease (CD) are frequently associated and share the ancestral haplotype human leukocyte antigen (HLA)-8.1, which is characterized by a peculiar cytokine profile. The aim of this study was to evaluate the role of tumor necrosis factor (TNF) and interleukin (IL)-10 alleles in CD and CD-IgAD. The distribution of some biallelic polymorphisms of both cytokine promoters (−308G→A and −863C→A at TNF promoter sequence and −1082G→A, −819C→A, and −592C→T at IL-10 promoter) were typed using biotilinated specific probes in 32 celiac patients, in 34 CD-IgAD patients, and in 96 healthy controls. In CD and CD-IgAD, the −308A allele was significantly more frequent than in controls, whereas no significant differences were observed for the biallelic polymorphisms at the −863 and for the three IL-10 promoter polymorphisms. The evaluation of combined TNF and IL-10 genotypes showed in CD-IgAD a significant reduction of −308G/−1082G homozygous subjects and both in CD and CD-IgAD groups an increase of 308AA/1082GG. Accordingly, CD-IgAD patients positive both for −308A TNF and −1082A IL-10 showed an increase of TNF-α and a reduction of IL-10 serum levels. Genetically determined increased production of TNF-α and reduction of IL-10 may be relevant for susceptibility to CD, mainly in IgAD, as the different allele expression at TNF and IL-10 loci seems to influence cytokine production profile.